ANALISIS LINGKUNGAN DAN PERILAKU MASYARAKAT YANG BERPENGARUH TERHADAP KEJADIAN MALARIA DI WILAYAH KERJA PUSKESMAS HANURA TAHUN 2022 - Billal Anugrah Putra; Lolita Sary; Agung Aji Perdana (Public Health Department, Faculty of Health Science University Muhammadiyah Bengkulu, 2022)
Background, Malaria cases are expected in the Pesawaran district, especially in Hanura Public Health Center in the Teluk Pandan sub-district. The Malaria case from January to October 2021 is higher than in 2020. There is a reasonably high increase, with 308 points happening in 2021. This research aims to determine the environmental and behaviors factors of the Malaria case in the Hanura Public Health Center in Teluk Pandan sub-district, Pesawaran district. Method, This research uses qualitative research with a Case-Control design, and the samples of this research were each 48 case and control groups. The sampling techniques used in this research are purposive sampling combined with univariate and bivariate analysis tests with chi square to determine the correlation between the independent and dependent variables and the Odds Ratio. Results. This research results show no significant behavior (p-value : 1.000: OR: 1.410: 95% CI: 624-3.185), temperature (p-value : 0.058: OR: 2.477: 95% CI: 1.057-5.807) with the incidence of Malaria. Conclusion It is necessary to do further research, both with the same and different designs, instrumen and variables..